Advances in plant glycosides, chemistry and biology : proceedings of the International Symposium on Plant Glycosides, August 12-15, 1997 Kunming, China - International Symposium on Plant Glycosides (1997 : Kunming, China); Yang, Chong-Ren.; Tanaka, Osamu; ScienceDirect eBooks (Amsterdam ; New York : Elsevier, 1999)
In the plant kingdom a variety of chemical constituents occur in a glycoside form (conjugation with sugar). Glycosides are important, secondary metabolites. The structural diversity is a result of the vast amount of varieties and stereochemical configurations of the sugar component. Aglycones belong to terpenoid, steroid, flavonoid, quinonoid, lignan, other simple phenolics, and isothiocyanate. However, biological activities of glycosides are, in many cases, susceptible to the nature of sugar moieties, even though their aglycone is the same. Since the 80s, plant glycosides have been attracting an increasing volume of interest from botanists and phytochemists world-wide for the following reasons: & bull; They are difficult to isolate and purify & bull; They have a very important biological function in plant life and remarkable biological activities & bull; They are a very important resource of natural medicine, health food, cosmetics and food supplements. The first International Symposium on Plant Glycosides (ISPG), held in Kunming, China was attended by more than 150 scientists from 17 countries. During the four day meeting, 96 reports on plant glycosides, including structure elucidation, ethnobotany, pharmacology, quantitative evaluation, synthesis, pharmacology and biotechnology were presented. 54 of these papers are given in this volume. All these papers review recent research results on plant glycosides.
Selected Papers. Significance of glycosides in food materials (O. Tanaka). Cancer chemopreventive activities of Panax notoginseng and Ginsenoside Rg1 (T. Konoshima). NMR studies on sugar moieties of some new triterpenoid saponins from Aralia spinifolia and Nothopanax davidii (S.-S. Yu et al.). Formation of Ginsenoside-protein conjugates (H. Park et al.). Biological test on Schefflera glycosides and Ginseng glycosides by radio-ligand receptor binding assays (M. Zhu, R.C. Li). Leguminous glycosides effective for hepatitis (T. Nohara, J. Kinjo). Review of studies on biological activities of soyasaponins (Z.-Z. Qian et al.). Synthesis of steroid saponins from Chinese herbs (B. Yu et al.). Rapid determination on plant glycosides by LC/MS and LC/NMR (K. Hostettmann, J.-L. Wolfender). Separation of three major isoflavonoids from the root of Fueraria Lobata by high speed centrifugal partition chromatography (Y.-H. Pei et al.). Structural analyses of glycolipids from edible mushroom by fast atom bombardment mass spectrometry (A. Sawabe et al.). Contributors. Latin Name Index.
Includes index.
Print version record.
Includes bibliographical references and index.
Elsevier
Keywords: Glycosides -- Congresses; Glycosides -- Physiological effect -- Congresses; Botanical chemistry -- Congresses; SCIENCE -- Life Sciences -- Biochemistry; Botanical chemistry; Glycosides; Glycosides -- Physiological effect; Electronic books